Anti-oxidant ebselen delays microvascular thrombus formation in the rat cremaster muscle by inhibiting platelet P-selectin expression - Lindenblatt, Nicole; Schareck, Wolfgang; Belusa, Lorenz; Nickels, Ruth Maria; Menger, Michael Dieter; Vollmar, Brigitte (Thrombosis and Haemostasis, 2003)
Ebselen, a seleno-organic compound showing glutathione peroxidase-like activity, has potent anti-inflammatory and anti-oxidant effects. Since selenium deficiency is thought to be associated with an increased incidence of vascular thrombosis, we studied the effect of ebselen on blood cell aggregate formation and vessel occlusion in vivo. In individual microvessels of rat cremaster muscle preparations, photochemically induced thrombus formation was analyzed in detail using intravital fluorescence microscopy. In ebselen-pretreated animals (30mg/kg ip), venular thrombus formation was significantly delayed (50% vessel occlusion: 535±34s; initial stasis: 872±82s; complete occlusion: 908±87s) as compared to vehicle-treated controls (416±42; 612±49; 647±51). Moreover, ebselen significantly prolonged the kinetics of arteriolar thrombus formation and even completely prevented blood cell aggregate and thrombus formation in 88.9% of all arterioles studied (p<0.05 vs controls:37.5%). Anti-thrombotic properties of ebselen could also be observed in a model of ferric chloride-induced microvascular thrombosis, with a low dose (5mg/kg ip) being as effective as a high dose pretreatment (30mg/kg ip). As assessed by flow cytometry of platelet P-selectin immunfluorescence, whole blood isolated from ebselen-treated animals revealed a significantly lower fraction of P-selectin expressing platelets when compared with that of DMSO-treated controls. In addition, oxidant stress-induced upregulation of P-selectin on isolated platelets was found dose-dependently inhibited by increasing concentrations of ebselen (10-100µM). Moreover, ebselen dose-dependently inhibited H2O2-induced platelet-leukocyte aggregate formation in whole blood in vitro, suggesting that the anti-thrombotic effect of ebselen is achieved by attenuation of P-selectin dependent platelet-leukocyte aggregation. Thus, ebselen represents preventive and therapeutic value for disorders with increased risk for oxidant stress-associated thrombotic events.
Keywords: Thrombosis; platelet; leukocyte; fluorescence microscopy; flow cytometry; oxidant stress